1999
DOI: 10.1093/humrep/14.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte quality and treatment outcome in intracytoplasmic sperm injection cycles of polycystic ovarian syndrome patients

Abstract: Patients with polycystic ovarian syndrome (PCOS) have higher miscarriage rates. It is postulated that this is caused by a lower rate of mature oocytes, and a lower quality of embryos. Retrospectively we analysed 51 intracytoplasmic sperm injection (ICSI) cycles of 31 PCOS patients. These data were compared to age-matched controls (105 cycles) during the same period. All patients of both groups received gonadotrophin-releasing hormone (GnRH) agonists prior to gonadotrophin treatment. The rate of metaphase II oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 22 publications
7
70
1
7
Order By: Relevance
“…The literature contains several studies that report that oocyte maturation is impaired in PCOS (20), oocyte quality and fertilization capacities are reduced (21), and, in addition, obesity contributes to such impaired maturation in PCOS (22)(23)(24). Fedorcsák et al (9) reported that the number of oocytes retrieved was low in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains several studies that report that oocyte maturation is impaired in PCOS (20), oocyte quality and fertilization capacities are reduced (21), and, in addition, obesity contributes to such impaired maturation in PCOS (22)(23)(24). Fedorcsák et al (9) reported that the number of oocytes retrieved was low in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased LH concentrations result in estradiol production impairment, follicle selection derangement, inability of luteinization and ovulation after hCG administration [46]. Increased LH concentrations are believed to be responsible for poor oocytes quality, low fertilization rate and high miscarriage percentage in patients with PCOS [47,48]. Optimal concentration of LH needed to most favorable COH became the subject of many studies and discussions.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive performance of women undergoing IVF treatment with PCOS is characterized by their good response to ovarian stimulation that yields higher number of oocytes; however, with lower implantation and higher miscarriage rates (Engmann et al 1999, Ludwig et al 1999, Mulders et al 2003. Individual oocytes retrieved from nine women with PCOS and that from ten non-hirsute ovulatory women are used for microarray hybridization (Wood et al 2007).…”
Section: Global Gene Expression Changes During Loss Of Oocyte Qualitymentioning
confidence: 99%